Implementation of OSS Application-Based Licensing Services at the Investment Office and One-Stop Integrated Licensing Services of Langkat Regency - Leli Afrida; Nina Siti Salmaniah Siregar; Budi Hartono (Journal of Social Interactions and Humanities, 2024)
This study discusses the implementation of OSS Application-Based Licensing Services at the Investment Office and One-Stop Integrated Services of Langkat Regency and its inhibiting factors. Public services in Indonesia are aimed at improving the relationship between the state and society. The research method uses a qualitative approach with a focus on analyzing relevant aspects as well as community satisfaction surveys. Data were obtained through direct observation, interviews, and literature studies. The results showed that OSS has had a positive impact in facilitating the licensing process for the community and business actors in Langkat Regency. However, several inhibiting factors such as inadequate technology infrastructure, lack of understanding of licensing requirements, and legal issues need to be addressed. By addressing these factors, DPMPTSP can improve efficiency and support regional economic growth.